A comparative study of air filters in air conditioning industry / Marfuza Omar and Maziah Suraya Abd Majid - Omar, Marfuza; Abd Majid, Maziah Suraya (2002)
The thesis is about comparative study of air filters in air conditioning industry. The objective of this thesis is to study the various types of air filters in air-conditioning industry. This thesis deals with various types of filters such as panel filters, roll filters and bag filters. Study on these types of filters based on type, efficiency, design, material, mechanism and application. The main content of this thesis contain introduction, comparison and conclusion. Besides that, we have gone to the suppliers of air filters to get some information and materials such as the filter samples, catalogs and so on. After doing a thorough study, we learned about filter efficiency, designs and filters materials and various applications and mechanism.